Analysis of Neutrophil Gelatinase-Associated Lipocalin in Type 2 Diabetes Mellitus Patients - Yunita Rapa'; Liong Boy Kurniawan; Asvin Nurulita; Fitriani Mangarengi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Neutrophil Gelatinase-Associated Lipocalin (NGAL) is a small protein with a molecular weight of 21 kDa, belongs to the lipocalin protein family and functions as a growth factor and differentiation of various cell types such as renal tubular epithelial cells. This aim of study was to determine the level of NGAL in controlled and uncontrolled type 2 Diabetes Mellitus (DM) patients. This study was a cross sectional study involving 70 type 2 DM patients with 30 patients with controlled type 2 DM and 40 uncontrolled type 2 DM groups. HbA1c, urea, creatinine, and urinalysis data were measured. NGAL level was measured using the ELISA method. The statistical tests used were Chi-Square, unpaired T test, Mann-Whitney test and Spearman test. The test result is significant if the p-value <0.05. NGAL normally found in the circulation will be filtered by the glomerulus and reabsorbed by the epithelial cells of the proximal renal tubule. Increased levels of NGAL can be found 2-6 hours in the blood and urine after injury to the kidneys. Excretion of NGAL in blood occurs when there is damage to the epithelial cells of the proximal tubule of the kidney. There was a significant difference in NGAL levels in the controlled and uncontrolled groups of type 2 DM patients. Positive correlation indicates that the higher the HbA1c and creatinine levels, the higher the NGAL level. There was a significant difference in NGAL levels in the controlled and uncontrolled type 2 DM groups (25.09 ± 6.83 vs 112.54 ± 170.38 ng / mL, with p value <0.001). There was a positive correlation between NGAL and HbA1c levels with p value <0.001, r =0.507 and creatinine levels with p value <0.001, r =0.769. NGAL normally found in the circulation will be filtered by the glomerulus and reabsorbed by the epithelial cells of the proximal renal tubule. Increased levels of NGAL can be found 2-6 hours in the blood and urine after injury to the kidneys. Excretion of NGAL in blood occurs when there is damage to the epithelial cells of the proximal tubule of the kidney. There was a significant difference in NGAL levels in the controlled and uncontrolled groups of type 2 DM patients. Positive correlation indicates that the higher the HbA1c and creatinine levels, the higher the NGAL level.